A Model Questionnaire for Evaluation of Musculo Skeletal Disorder - Kar, Sanjit Kumar (Journal of Universal College of Medical Sciences, 2018)
Occupational health hazards are the very important unavoidable problems of different type of jobs. All occupational jobs contain several tasks and workers are compelled to adopt some harmful and awkward postures during performing those tasks. These types of repetitive jobs may be related to occupational health hazards like musculo skeletal disorder (MSD). In the present methodology different MSD related problems of the workers can be assessed by the questionnaire techniques considering the issues of community health development. In this concern a simple and easily applicable questionnaire technique has been established for the different occupations during performing tasks. It was concluded that MSD among the workers might be related to the stressful work posture, long duration jobs, nature of jobs and use of ill-fitted hand tools. So, with the application of the questionnaire, investigator can evaluate the real physiological problems and give them remedies. Journal of Universal College of Medical Sciences (2016) Vol.04 No.02 Issue 14, page: 46-48